MENCAPAI EFEKTIVITAS PROGRAM PEMBERDAYAAN MELALUI TECHNOLOGY OF PARTICIPATION (ToP): STUDI KASUS DI DESA CISAMBENG KABUPATEN MAJALENGKA - Brelyantika Indra Jesa; Muhammad Ilham Fahmi (Journal of Appropriate Technology for Community Services, 2020)
Community empowerment is a process towards being empowered by actively involving society. There have been empowerment programs that failed because of no community's participation inside the programs. The effectiveness of a community empowerment program is depend on the level of community participation in it. This happened because society knows their needs, problems, and potential. An effort to achieve the effectiveness of community empowerment is needed technique to achieve ideal conditions reached easier. One of the techniques that can be used is Technology of Participation (ToP). The technology of Participation is a technique that assists in making decisions with a participatory approach. This research has aim to describe the benefits of using the Technology of Participation in community empowerment programs. This research uses a qualitative approach with a case study method. The case study design used is a single-case design that focuses on empowerment programs that carried out in Cisambeng Village. This result of this research shows that there is a different community response to participation in empowerment Participation (ToP).